Effective Learning to Build Science Literacy: A Meta-Analysis Study - Fajar, Annur; Supriyadi, Supriyadi; Pratama, Anisa Oktina Sari (Universitas Sang Bumi Ruwa Jurai, 2025)
The science literacy of students in Indonesia, based on the PISA 2022 assessment, is categorized as low. Indonesia ranks 67th out of 81 countries, indicating that science literacy still needs significant improvement. This study aims to identify the most effective learning model for improving science literacy and to understand its characteristics. The method used is meta-analysis, consisting of four stages: data collection, data reduction, data presentation, and conclusion drawing. The data analyzed were obtained from nine national journal articles published between 2020 and 2024, sourced from Google Scholar, Publish or Perish, Garuda, and Sinta. The results of the analysis show that the Discovery Learning model has the highest effect size value of 4.14, indicating that it is highly effective in improving science literacy. This model actively involves students in the process of discovering concepts through observation, data processing, and drawing conclusions, thereby developing critical thinking skills and the ability to solve problems independently. The average effect size values across Indonesian regions vary significantly, with western Indonesia showing an average of 1.51 and eastern Indonesia 1.64. The average effect size at different education levels was found to be 2.06 at the junior high school level and 0.90 at the high school level. Similarly, the effect size for the topic of interactions among living things taught to junior high school students was 4.14, while for high school students, the effect size for the topic of climate change was 2.42.